Editorial - Vedula, Krishna (Journal of Engineering Education Transformations, 2018)
In the first 3 months of 2018, JEET has received more than 20 articles submitted for review. In most cases, the plagiarism check was conducted within 1 week, and the initial editorial check was conducted within 2 weeks of submission. Reviewer assignment took place within 3 weeks of submission, and editorial decisions within 8 weeks. With a growing number of articles submitted to the journal, 28 new reviewers were added to the review team We are pleased to welcome Dr. Gopal Joshi and Dr. Prathiba Nagabhushan to the editorial board, and we expect to appoint a few more associate editors. Please contact Dr. Sohum Sohoni (sohum.sohoni@asu.edu) if you would like to be considered for appointment as associate editor.